2018
DOI: 10.1111/acel.12764
|View full text |Cite
|
Sign up to set email alerts
|

Advanced oxidation protein products induce pre‐osteoblast apoptosis through a nicotinamide adenine dinucleotide phosphate oxidase‐dependent, mitogen‐activated protein kinases‐mediated intrinsic apoptosis pathway

Abstract: SummaryOsteoblast apoptosis contributes to age‐related bone loss. Advanced oxidation protein products (AOPPs) are recognized as the markers of oxidative stress and potent inducers of apoptosis. We have demonstrated that AOPP accumulation was correlated with age‐related bone loss. However, the effect of AOPPs on the osteoblast apoptosis still remains unknown. Exposure of osteoblastic MC3T3‐E1 cells to AOPPs caused the excessive generation of reactive oxygen species (ROS) by activating nicotinamide adenine dinuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 42 publications
5
57
0
1
Order By: Relevance
“…According to previous reports, NADPH oxidase is regarded as one of the main sources of ROS production that plays a pivotal role as a modulator in ROSmediated oxidative damage in many kinds of cells. It has been well demonstrated that AOPPs could induce ROS generation by sensitizing NADPH oxidase [37][38][39]. In general, 5 isoforms of NADPH oxidase (NOX) family have been identified (NOX1, 2, 3, and 4, and DUOX 2), and are shown to express in the spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous reports, NADPH oxidase is regarded as one of the main sources of ROS production that plays a pivotal role as a modulator in ROSmediated oxidative damage in many kinds of cells. It has been well demonstrated that AOPPs could induce ROS generation by sensitizing NADPH oxidase [37][38][39]. In general, 5 isoforms of NADPH oxidase (NOX) family have been identified (NOX1, 2, 3, and 4, and DUOX 2), and are shown to express in the spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…However, increased ROS production in osteoblasts will exceed the osteoblast antioxidant capacity and accelerate apoptosis [44]. MAPKs are widely recognized as major cell signaling molecules in ROS-induced apoptosis [1921]. However, the specific molecular mechanisms in osteoblasts have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis, or cell death, occurs when ROS production exceeds its elimination ability [18]. In addition, there is strong evidence that mitogen-activated protein kinases (MAPKs) are closely related to ROS-induced apoptosis [1921]. However, NOX/NADPH oxidase isoform involvement in the pathogenesis of ROS generation and the apoptosis signaling molecules in osteoblasts induced by high-dose dexamethasone (DEX) has not been fully clarified.…”
Section: Introductionmentioning
confidence: 99%
“…The increase of ROS in osteoblastic MC3T3-E1 cells induced phosphorylation of MAPKs (mitogen-activated protein kinases), which subsequently triggered the intrinsic apoptosis pathway. Moreover, the advanced oxidation protein products induced osteoblast apoptosis in aged Sprague–Dawley rats [ 30 ].…”
Section: Osteopenia/osteoporosismentioning
confidence: 99%